Analysis and source identification of dust event in Khuzestan province using MODIS and SENTINEL satellite data and HYSPLIT model (2018–2022) - Alireza Yousefi Kebriya; Mehdi Nadi; Ebadat Ghanbari Parmehr; Zhongchang Sun (PLoS ONE, 2026)
Dust events present significant environmental and public health challenges in Khuzestan Province, Iran, severely affecting air quality, human health, and ecosystems. This study analyzed dust dynamics from 2018 to 2022 using satellite-derived Aerosol Optical Depth (AOD), Aerosol Absorption Index (AAI), ground-based PM₂.₅ and PM₁₀ data, HYSPLIT trajectory modeling, wind rose analysis, and wetland assessments. Strong correlations were found between AOD and PM₂.₅ (R² = 0.79) and PM₁₀ (R² = 0.91), confirming the reliability of satellite monitoring. PM₂.₅ ranged 12–750 µg/m³ and PM₁₀ 10–800 µg/m³, with peaks linked to drought, wetland shrinkage, and transboundary inflows. AOD-Max reached 3.2–3.9, with temporal variability reflecting flooding and drought events. Annual trajectory clustering identified six major dust pathways to Ahvaz; the primary route (43.48%) crossed eastern Iraq and Hoor al-Azim, with 65.2% of pathways traversing Iraqi deserts. Weighted Potential Source Contribution Function (WPSCF) and Weighted Concentration Weighted Trajectory (WCWT) mapping revealed a northwest–southeast dust belt across Iraq (AOD 0.6–0.8, locally >1.0) and secondary zones in southern Iraq, the Khuzestan border, eastern Syria, and Ninawa (AOD 0.4–0.6, rising to 0.6–0.9). Dust reached Ahvaz within 24 hours, with strong AOD correlations (R² = 0.85–0.75; 2018–2022). The Hoor al-Azim Wetland contracted dramatically from ~2,000 km² (>5 m water) in 2019 to ~73 km² (1.2–2.9 m) in July 2022, with low MNDWI values (0.33 to −0.29). Wetland area correlated strongly with AOD (R² = 0.78) and water level (R² = 0.71). Three hydrological–air quality states emerged: healthy (~1,100–2,000 km², AOD < 0.4), transitional (400–1,000 km², AOD 0.4–1.0), and critical (<250 km², AOD > 1.0, up to ~1.7), with a ~ 500 km² threshold marking sharp reduction in dust suppression. These findings highlight the urgent need for wetland restoration, desertification control, and transboundary cooperation to mitigate dust risks in the region.